2020
DOI: 10.2807/1560-7917.es.2020.25.12.2000334
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of regional SARS-CoV-2 community transmission through a convenience sample of healthcare workers, the Netherlands, March 2020

Abstract: To rapidly assess possible community transmission in Noord-Brabant, the Netherlands, healthcare workers (HCW) with mild respiratory complaints and without epidemiological link (contact with confirmed case or visited areas with active circulation) were tested for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Within 2 days, 1,097 HCW in nine hospitals were tested; 45 (4.1%) were positive. Of six hospitals with positive HCW, two accounted for 38 positive HCW. The results informed local and nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 2 publications
6
99
1
6
Order By: Relevance
“…As expected, this prevalence value is significantly lower than that reported in symptomatic HCWs from Wisconsin (7) and in operating in COVID19 structures experience (12). As far as we know, this is the only study considering asymptomatic HCWs from a non-Covid19 cancer Institute in which, however, a recent activated screening program for all hospitalized patients reported 1% of patients positive for SARS-COV2 (promptly transferred to specific COVID19 hospitals).…”
Section: Interassay Comparison All Subjetcs With Non-negativementioning
confidence: 49%
“…As expected, this prevalence value is significantly lower than that reported in symptomatic HCWs from Wisconsin (7) and in operating in COVID19 structures experience (12). As far as we know, this is the only study considering asymptomatic HCWs from a non-Covid19 cancer Institute in which, however, a recent activated screening program for all hospitalized patients reported 1% of patients positive for SARS-COV2 (promptly transferred to specific COVID19 hospitals).…”
Section: Interassay Comparison All Subjetcs With Non-negativementioning
confidence: 49%
“…On the frontlines of defense against the virus, HCW may experience increased risk of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection due to close contact with highly infectious patients 1 and, commonly, insufficient access to personal protective equipment (PPE) 2 . The plight of HCW during the pandemic has been widely noted [3][4][5][6][7][8] ; as of April 9, 2020, 9,282 known COVID-19 cases among U.S. HCW had been reported to the Centers for Disease Control and Prevention (CDC) 9 . Of HCW with COVID-19, 55% reported that their only known exposure was the in the health care setting.…”
Section: Introductionmentioning
confidence: 99%
“…Our results predict that Sweden's healthcare capacity (both for COVID-19 patients and for others) will be rapidly overwhelmed under the current strategy, both through the need to care for COVID-19 patients and because healthcare workers will themselves become ill and unable to work. [41][42][43][44][45][46][47][48][49] Intensive care capacity is projected to become a particular bottleneck, as shown in other countries. [50][51][52] For Sweden, this is in particular worrisome considering the relatively low availability of beds prior to the pandemic compared to other European countries 22 24 and recent reports challenging Swedish disaster preparedness.…”
Section: Meaning Of the Study: Possible Explanations And Implicationsmentioning
confidence: 99%